Hotel and motel management and operations - Gray, William S.; Liguori, Salvatore C. (Singapore : Pearson Education South Asia Pte Ltd, 2003)
Written in an easy-to-understand style, this book provides comprehensive information on every facet and department of the hotel. Property management system operation is discussed, with sample reports for students. The operation of restaurant point of sale systems is also discussed, with related sample reports included.
I. HOTEL AND MOTEL DEVELOPMENT. 1. The History of the Hospitality Industry. 2. Types of Hotels. 3. Corporate Structures and Concepts of Operation. 4. Feasibility Determination. II. HOTEL MANAGEMENT. 5. Hotel Structure and Staff. 6. The Human Resources Department. 7. Reservations: Systems and Operations. 8. Sales and Marketing. III. HOTEL OPERATIONS. 9. The Front Office. 10. Food and Beverage Preparation and Service. 11. Telecommunications. 12. Engineering. 13. Housekeeping. 14. Other Departments and Sources of Income. 15. Insurance. IV. HOTEL ACCOUNTING AND CONTROLS. 16. The Organization of Accounting and the Uniform System. 17. Accounts Receivable and City Ledger. 18. Income Control. 19. Food and Beverage Cost Control. 20. Payroll. 21. Accounts Payable. 22. Credit. 23. Other Responsibilities of the Accounting Department Including Financial Statements. V. THE FUTURE OF THE INDUSTRY. 24. Franchising. 25. Casinos. 26. Health Spas. 27. Trends in the Industry.
Includes index.
Keywords: HOTEL HOUSEKEEPING -- MANAGEMENT